21. Rozwiąż równania: a) 12 – 2 * (x – 1) ^ 2 = 4(x – 2) – (x – 3)(2x – 5) b) (3x – 1) ^ 2 – 5 * (2x + 1) ^ 2 + (6x – 3)(2x + 1) = (x – 1) ^ 2 c) 5 * (x – 1) ^ 2 – 2 * (x + 3) ^ 2 = 3 * (x + 2) ^ 2 – 7(6x – 1) d) 2x ^ 2 + (x + 5) ^ 2 – 2 * (x + 7) ^ 2 = 2(3x – 72, 5) + (x – 6) ^ 2

21. Rozwiąż równania: a) 12 – 2 * (x – 1) ^ 2 = 4(x – 2) – (x – 3)(2x – 5) b) (3x – 1) ^ 2 – 5 * (2x + 1) ^ 2 + (6x – 3)(2x + 1) = (x – 1) ^ 2 c) 5 * (x – 1) ^ 2 – 2 * (x + 3) ^ 2 = 3 * (x + 2) ^ 2 – 7(6x – 1) d) 2x ^ 2 + (x + 5) ^ 2 – 2 * (x + 7) ^ 2 = 2(3x – 72, 5) + (x – 6) ^ 2